Effects of Transient Electrical Acupuncture Stimulation Combined With Rehabilitation Training on Hemorheology, Neurological Function and BDNF in Patients With Cerebral Infarction - Chen, Shuangqin; Huang, Jianghua; Tang, Xuan; Wang, Ting; Zeng, Yahua (Frontiers in Surgery, 2022)
【Abstract】Objective To explore the effects of transient electric acupuncture stimulation combined with rehabilitation training on hemorheology, neurological function and BDNF in patients with cerebral infarction. Methods A total of 90 patients with cerebral infarction were admitted to our hospital from March 2019 to March 2021. According to the random number table method, 90 patients were divided into a control group and a treatment group, with 45 cases in each group. NIHSS score to detect neurological deficit; FMA score to detect motor function recovery; compare the clinical efficacy of the two groups of patients; blood rheology analyzer to detect whole blood high shear viscosity, whole blood low shear viscosity, platelet aggregation rate and fibrinogen indicators; ELISA detects the content of BDNF in serum. Results There was no significant difference in NIHSS score, FMA score, clinical efficacy, hemorheology index, and BDNF content between the two groups of patients before treatment (P>0.05). Compared before and after treatment, the NIHSS score of the two groups was lower than before treatment. FMA score was higher than before treatment, whole blood high shear viscosity, whole blood low shear viscosity, platelet aggregation rate and fibrinogen index were lower than before treatment, clinical efficacy and serum BDNF content were higher than before treatment (P<0.05) After treatment, the NIHSS score of the patients in the treatment group was lower than that of the control group, and the FMA score was higher than that of the control group. Whole blood high shear viscosity, whole blood low shear viscosity, platelet aggregation rate and fibrinogen index were lower than those of the control group. The clinical efficacy and serum BDNF content were higher than those of the control group (P<0.05). Conclusion The combination of transient electrical acupuncture stimulation and rehabilitation training can inhibit the blood flow index of patients with cerebral infarction, improve the nerve function, increase the content of BDNF in the patient's serum, and restore the patient's nerve function.